Values in the field of education and education - GUONI, Abdelbasset (Social Sciences Journal)
While there is no doubt that values have an important role in shaping the personality of the individual in an effective formation in its maturity and crystallization in different life situations, the function of the school is serious and is distinguished by its subject, which is the person who embraces him in the most important stages of his life, and the school is distinguished by its tools and means, which are knowledge and values, and its goals that are Formation of a righteous and reformed person who carries knowledge, values and principles, and therefore the wager is based on the educational institution in achieving that goal, but the development of values in the school today raises several problems, whether at the level of the relationship of values to practice, or at the level of its pedagogical and methodological approach, and its consecration In school life, this problem is represented in terms of practice, how the school achieves its educational function in socialization, through methods of delivering curricula and educational and training programs with all their human, social and psychological components. Among the educational institutions interested in this practice (the acquisition of values) is the school or the fortified castle of society that preserves its existence and survival, through its various educational curricula. Education is what determines the general ideology of society or what is called the general educational policy of the state, and it is what generates an educational value system that it implants in its educated members